Efficacy of outdoor interventions for myopia in children and adolescents: a systematic review and meta-analysis of randomized controlled trials - Mei, Zhengyang; Zhang, Yuanzhuo; Jiang, Wenfeng; Lam, Chifong; Luo, Shulai; Cai, Chenyi; Luo, Shi (Frontiers in public health, 2024)
The objective of this systematic review and meta-analysis was to evaluate the overall efficacy of outdoor interventions for myopia in children and adolescents, and to provide evidence for the prevention and control of myopia. Randomized controlled trials of outdoor interventions for myopia in children and adolescents were identified using electronic databases and manual searches. The Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) was used to assess risk of bias in randomized controlled trials. A mean difference (MD) and a risk ratio (RR) with a 95% confidence interval (CI) were used to combine effect sizes. A sensitivity analysis was performed for each outcome using a stepwise elimination method to assess whether the pooled results were significantly affected by individual studies. The analysis included seven randomized controlled trials involving a total of 9,437 subjects. The meta-analysis showed marked and statistically significant improvements in spherical equivalent refraction (MD = 0.19; 95% CI 0.14 to 0.25; < 0.01), axial length (MD = -0.09; 95% CI -0.13 to -0.05; < 0.01), and myopia incidence (RR = 0.84; 95% CI 0.78 to 0.91; < 0.01) following outdoor interventions. Outdoor interventions effectively contributed to the prevention and control of myopia in children and adolescents, positively impacting spherical equivalent refraction, axial length, and myopia incidence. Outdoor interventions were characterized by low risk and high therapeutic benefits and could serve as alternative or adjuvant approaches to medication for the treatment of myopia. Considering the advantages in terms of safety and efficacy, outdoor interventions may be considered as a preferred intervention for the treatment of myopia in children and adolescents, while susceptibility to diseases associated with sunlight, particularly UV exposure, must be taken into account. https://www.crd.york.ac.uk/prospero/, Identifier CRD42024538695.